The intergenerational effects of parental incarceration - Hans Grönqvist; Susan Niknami; Mårten Palme; Mikael Priks (Research Institute of Industrial Economics (IFN), 2024)
We estimate the causal effects of parental incarceration on children's short- and long-run outcomes using administrative data from Sweden. Our empirical strategy exploits exogenous variation in parental incarceration from the random assignment of criminal defendants to judges with different incarceration tendencies. We find that the incarceration of a parent in childhood leads to a significant increase in teen criminal convictions, a decrease in high school graduation, and worse labor market outcomes in adulthood. The effects are concentrated among children from disadvantaged families, in particular families where the remaining non-convicted parent is disadvantaged. These results suggest that the incarceration of parents with young children may significantly increase the intergenerational persistence of poverty and criminal behavior in affluent countries with extensive social safety nets and progressive criminal justice systems.
Keywords: K42; 330; Crime; Parental incarceration; Children's outcomes; School graduation; Labor market